The Effect Of Implementing VCT (Value Clarification Technique) Learning Model On Students Affection In History Subject In Grade X Of Sma Negeri 16 Palembang - Devi Permatasari; Hudaidah Hudaidah; Sani Safitri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
This Study entitled “The Influence Of Vct (Value Clarification Technique) Learning Model Application For Students Affection Of History Lesson In X Class Senior High School 16 Palembang”. Problem in this research is there anything influence of VCT (Value Clarification Technique) Learning Model Application For Students Affection of History Lesson In X Class Senior High School 16 Palembang. This research has been carried out on Maret 03 until April 30, 2017. The sample in this research is class X IPA 1 and X IPA 3. Determination of classes taken by simple random sampling. Data collection technics using by data normality test, homogeneity test and Anava One Way. This questionnaire has more results for agreement alternative. By doing analysis data we got. 1) Fhitung = 3,95 > Ftabel = 2,49 so Ha was accepted and Ho was rejected. 2) Fhitung = 2,70 > Ftabel = 4,10 so Ha was rejected and Ho was accepted. 3) Fhitung= 2,34 > Ftabel 2,31 so Ha accepted and Ho rejected. Because the level relation between those variable is strong, so the concluion is there are influence from VCT (Value Clarification Technique) learning model application for students affection of history lesson in X class Senior High School 16 Palembang.